Innovative method of non-contact electric field energy harvesting under 275kV power transmission line - Yeesparan S.; Baharuddin M.Z.; Din N.M.; Haron M.H. (Alpha Publishers, 2023)
Advance technologies in todays world gradually developing and bringing many innovative products and findings. One of the improving technologies of all time are energy harvesting. With a massive amount of external sources, energy harvesting can be a prominent and alternative solution to provide power supply without batteries in a more cost effective at the same time environment friendly way. In this paper, a new method of harvesting electric field under 275kV transmission line is applied by using innovative design of non-contact electric field energy harvester (EFEH). Seven significant design parameters such as the capacitance of the harvester, the material and thickness of harvester and the surface nature of the harvester are examined and improved step by step ensuring an efficient, cost effective and less complaicated EFEH design. ANSYS Maxwell software is used to simulate, analyse and compare the electric field captured on each designs. In order to support the electric field simulations of all the harvester designs, EFEH prototypes are built and tested under a 275kV electrical transmission lines surroundings. A maximum of 14.5V of AC voltage from the harvester and 7uW of output power is recorded from the most efficient EFEH design using a simple half wave rectifier 10uF capacitor in filter. The proposed EFEH can be implemented to energize low powered sensors that are used to monitor conditions of electrical transmission lines and the vicinity surrounding the tower especially in areas that cannot be easily accessed by people. 2020 Alpha Publishers.